Letterboxed : the evolution of widescreen cinema - Cossar, Harper (UPCC book collections on Project MUSE., 2011)
Exploring the technological changes of the widescreen technique and how the format has inspired directors and also sparked debates among film critics, Cossar also explains how directors use wider aspect ratios to enhance their creative visions.